e-SCP-ECG+ Protocol: An Expansion on SCP-ECG Protocol for Health Telemonitoring—Pilot Implementation - George J. Mandellos; Michael N. Koukias; Ioannis St. Styliadis; Dimitrios K. Lymberopoulos (International Journal of Telemedicine and Applications)
Standard Communication Protocol for Computer-assisted Electrocardiography (SCP-ECG) provides standardized communication among different ECG devices and medical information systems. This paper extends the use of this protocol in order to be included in health monitoring systems. It introduces new sections into SCP-ECG structure for transferring data for positioning, allergies, and five additional biosignals: noninvasive blood pressure (NiBP), body temperature (Temp), Carbon dioxide (CO2), blood oxygen saturation (SPO2), and pulse rate. It also introduces new tags in existing sections for transferring comprehensive demographic data. The proposed enhanced version is referred to as e-SCP-ECG+ protocol. This paper also considers the pilot implementation of the new protocol as a software component in a Health Telemonitoring System.